An experimental survey of metal artefact reduction in computed tomography - Mouton, Andre; Megherbi Bouallagui, Najla; Van Slambrouck, Katrien; Nuyts, Johan; Breckon, Toby P. (Elsevier, 2013)
We present a survey of techniques for the reduction of streaking artefacts caused by metallic objects in X-ray Computed Tomography (CT) images. A comprehensive review of the existing state-of- the-art Metal Artefact Reduction (MAR) techniques, drawn almost exclusively from the medical CT literature, is supported by an experimental comparison grounded in an evaluation based on a standard scienti c comparison protocol for MAR methods using a software generated medical phan- tom image. This experimental comparison is further extended by considering novel applications of CT imagery consisting of isolated metal objects with no surrounding tissue, as is encountered in typical engineering and security screening CT applications. We nd that the performance of twelve state-of-the-art MAR techniques to be fairly consistent across the two domains and demonstrate the feasibility of a reference-free quantitative performance measure. The literature review and experi- mentation demonstrate several trends. In particular, the major limitations of state-of-the-art MAR techniques are a dependence on prior knowledge, a sensitivity to input parameters and a shortage of comprehensive performance analyses. This study thus extends previous works by: comparing several state-of-the-art MAR techniques; considering both medical and non-medical applications and performing a comprehensive quantitative analysis, taking into account image quality as well as computational requirements.